PENDETEKSIAN DINI INTELIJEN DALAM MENCEGAH KONFLIK SOSIAL - Tubagus Anis Angkawijaya (Scientia Regendi, 2020)
The development of the global, regional strategic environment affects the security and public order, the dynamic conditions of social and social services in society are one of the prerequisites for the implementation of the national development process in order to achieve national goals which are marked by the assurance of security, order and the upholding of law, as well as the building of peace that contains capabilities. fostering and developing the potential and strength of the community in preventing, preventing and overcoming all forms of lawlessness and other forms of disturbance. In essence, kamtibmas is an essential need for every person or society who longs for a safe and orderly atmosphere in the order of life.